Air pollution driving factors analysis: Evidence from economically developed area in China. Issue 4 (21st February 2016) - Li, Wei; Sun, Shuang
Abstract : Rapid economic growth is usually accompanied by rising air pollution in China, especially in the economically developed regions. Beijing is the capital of China, which is selected as a study case in this article. The aim of this study is to authenticate if the Environmental Kuznets curve (EKC) hypothesis exists between air pollution and economic growth in Beijing over the period of 1990–2013, and to understand the driving factors of the air pollution by utilizing the Stochastic Impacts by Regression on Population, Affluence and Technology (STIRPAT) model. To avoid the multicollinearity of the driving factors, ridge regression is utilized. CO2, SO2 and dust emissions are served as the air pollution indicators. Results show that, both CO2 and SO2 emissions, contribute to an agreement to the EKC hypothesis, while dust emissions do not. Besides, the turning point of SO2 emissions has already achieved in 1999, whereas that of CO2 emissions will be achieved in 2026. Population, urbanization, and industry structure are introduced into the STIRPAT model. In the STIRPAT model, CO2, SO2 and dust emissions all follow the EKC hypothesis, while only SO2 emissions achieved the turning point in 2006, nevertheless, that of CO2 and dust emissions will be achieved in 2023 and 2070, respectively. Population, urbanization, and industry structure factors all contribute a positive impact on CO2 emissions. However, the three factors all exert negative influence on the SO2 and dust emissions. Finally, policies on addressing air pollution problems in Beijing have been discussed. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 1231–1239, 2016